GNPs / YSZ intelligent composite ceramic and preparation method and application thereof

By directionally controlling GNPs within YSZ ceramics through planetary ball milling and sintering, the composite ceramics maintain superior mechanical and radiation resistance, addressing the degradation issues of YSZ ceramics under radiation, ensuring enhanced reliability and longevity in extreme environments.

CN119638412APending Publication Date: 2025-03-18HARBIN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411993550.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Current YSZ ceramics used in aerospace suffer from mechanical property degradation due to hardening and embrittlement under radiation, leading to reduced long-term stability and reliability in extreme environments.

Method used

A method to prepare GNPs/YSZ intelligent composite ceramics with directionally controlled GNPs distribution within YSZ, utilizing planetary ball milling and subsequent sintering techniques to enhance mechanical and radiation resistance, maintaining superior toughness and hardness even after high-energy electron irradiation.

Benefits of technology

The GNPs/YSZ composite ceramics exhibit improved mechanical and radiation resistance, with enhanced hardness and toughness compared to pure YSZ, enabling extended service life and reliability in extreme environments, while being cost-effective and suitable for industrial-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638412A_ABST
    Figure CN119638412A_ABST
Patent Text Reader

Abstract

The invention discloses GNPs / YSZ intelligent composite ceramic as well as a preparation method and application thereof, a GNPs / YSZ composite ceramic block is formed by mixing GNPs powder and YSZ powder, and the direction of the GNPs in the YSZ ceramic is controllably arranged. The GNPs / YSZ intelligent composite ceramic material which still keeps excellent toughness after high-energy electron irradiation is prepared by utilizing the characteristics of excellent mechanics, electricity, heat conduction and the like of the GNPs, and the direction controllable arrangement of the GNPs in a YSZ matrix is realized by utilizing the anisotropy of the GNPs and a control preparation process. And by controlling the arrangement direction, the mechanical property of the surface can be optimized, which is extremely beneficial to surface protection application. The GNPs / YSZ intelligent composite ceramic material can be applied to extreme temperature and complex ground and space environments, the preparation method is simple, and industrial batch production can be quickly realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerospace materials, and relates to a GNPs / YSZ composite ceramic and a preparation method thereof, and specifically relates to a GNPs / YSZ intelligent composite ceramic and a preparation method and application thereof. Background Art

[0002] Yttria-stabilized zirconia (YSZ) ceramics have great potential for application in the aerospace field due to their excellent insulation, corrosion resistance, high temperature resistance and radiation resistance. In the field of nuclear irradiation, they can withstand high temperatures and radiation, and can also meet the irradiation requirements of various high-energy particles in extreme space. However, composite materials often harden and become brittle after irradiation, which reduces their mechanical properties and leads to reduced long-term service stability and reliability.

[0003] At present, although there are many reports on GNPs / YSZ composites, the preparation process is controlled to achieve controllable arrangement direction of GNPs in YSZ ceramics and the method for preparing a GNPs / YSZ smart composite ceramic has not yet been discovered. Summary of the invention

[0004] The present invention provides a GNPs / YSZ smart composite ceramic and its preparation method and application. By utilizing the excellent mechanical, electrical, thermal conductivity and other properties of GNPs themselves, a GNPs / YSZ smart composite ceramic material that still maintains excellent toughness after high-energy electron irradiation is prepared, and by utilizing the anisotropy of GNPs and the control of the preparation process, the direction-controlled arrangement of GNPs in the YSZ matrix is ​​achieved. By controlling the arrangement direction, the optimization of its surface mechanical properties can be achieved, which is extremely beneficial for surface protection applications. This GNPs / YSZ smart composite ceramic material can be used in extreme temperatures, complex ground and space environments, and the preparation method is simple, the equipment is common, the cost is low, and industrial mass production can be quickly achieved.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A GNPs / YSZ intelligent composite ceramic, wherein the GNPs / YSZ composite ceramic block is formed by mixing GNPs powder and YSZ powder, GNPs are arranged in the YSZ ceramic in a controllable direction, and the content of GNPs is 0.1-2wt.%.

[0007] A method for preparing the above-mentioned GNPs / YSZ smart composite ceramic comprises the following steps:

[0008] Step 1: Using a planetary ball mill, nano-scale GNPs powder, YSZ powder, and anhydrous ethanol are uniformly mixed to obtain a mixed solution, and then dried in a blast drying oven to obtain a GNPs / YSZ composite ceramic powder, wherein:

[0009] The YSZ powder is 4-8 mol% Y2O3 stabilized ZrO2, with a size of 10-100 nm;

[0010] The GNPs powder has a thickness of 1 to 3 nm, and a length and width of 500 nm to 1 μm;

[0011] The mass ratio of anhydrous ethanol to GNPs / YSZ composite powder is 1 to 3:1;

[0012] During the planetary ball milling, the ball-to-material mass ratio is 5-10:1, the ball milling time is 3-12 hours, and the rotation speed is 150-300 r / min;

[0013] The drying temperature is 50-100°C and the drying time is 12-24h;

[0014] Step 2: Sinter the dried GNPs / YSZ composite ceramic powder by spark plasma sintering technology or solid phase sintering technology after cold isostatic pressing to obtain a dense GNPs / YSZ composite ceramic block, wherein:

[0015] The spark plasma sintering temperature is 1200-1400°C, the heat preservation time is 2-10 minutes, the heating rate is 100-150°C / min, and the axial pressure is 30-60MPa;

[0016] The temperature of the solid phase sintering after cold isostatic pressing is 1200-1400°C, the temperature is kept for 1-2 hours, the heating rate is 5-15°C / min, and the cold isostatic pressing axial pressure is 200-400MPa;

[0017] In the GNPs / YSZ smart composite ceramic block, GNPs are arranged in a direction controllably in the YSZ ceramic, and the content of GNPs is 0.1-2wt.%. As the content of graphene nanosheets increases, the ability of the GNPs / YSZ composite ceramic block to withstand high-energy electron radiation increases first and then decreases.

[0018] The GNPs / YSZ intelligent composite ceramic block has a diameter of 20 to 25 mm and a thickness of 3 to 4.5 mm.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1. The present invention can achieve controllable direction and uniform dispersion in the YSZ composite ceramic block.

[0021] 2. The present invention can strengthen YSZ ceramics and improve mechanical and radiation resistance. After high-energy electron irradiation, the hardness and fracture toughness of the GNPs / YSZ smart composite ceramic blocks with the same content are increased compared with pure YSZ ceramics. It shows that after high-energy electron irradiation, its mechanical properties do not decrease but increase, and its radiation resistance is enhanced. It can be used in extreme irradiation environments such as high temperature and space irradiation to improve service reliability and stability and extend the service life of composite ceramics.

[0022] 3. The GNPs / YSZ smart composite ceramics of the present invention will be anisotropic, and for specific use environments, excellent properties in a certain direction are also an advantage.

[0023] 4. The GNPs / YSZ smart composite ceramics prepared by the present invention have low material cost, simple process and are easy to achieve mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The preparation flow chart of GNPs / YSZ smart composite ceramic block;

[0025] Figure 2 This is the arrangement diagram of graphene nanosheets in the GNPs / YSZ smart composite ceramic block;

[0026] Figure 3 XRD diagram of GNPs / YSZ smart composite ceramic powder;

[0027] Figure 4 Schematic diagram of hardness change of GNPs / YSZ smart composite ceramic block before and after high-energy electron irradiation;

[0028] Figure 5 Schematic diagram of the change in fracture toughness of GNPs / YSZ smart composite ceramic block before and after high-energy electron irradiation. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0030] Embodiment 1:

[0031] This embodiment provides a method for preparing a GNPs / YSZ smart composite ceramic. Figure 1 As shown, the method comprises the following steps:

[0032] Step 1: Using planetary ball milling, 99.6 g of nano-scale GNPs powder, 0.4 g of YSZ powder, and 300 ml of 99.7% anhydrous ethanol are uniformly mixed to obtain a mixed solution A, and then dried at 70°C for 24 hours in a blast drying oven to obtain a GNPs / YSZ composite ceramic powder, wherein: the YSZ powder is 8 mol% Y2O3-stabilized ZrO2 with a size of 30 nm; the GNPs powder has a thickness of 1 nm, and the length and width are 500 nm and 1 μm, respectively; during the planetary ball milling, the ball-to-material mass ratio is 10:1, the ball milling time is 4 hours, and the rotation speed is 150 r / min.

[0033] Step 2: Use spark plasma sintering technology to sinter the dried GNPs / YSZ composite ceramic powder to obtain a GNPs / YSZ intelligent composite ceramic block with a diameter of 25 mm and a thickness of 4 mm, wherein: the sintering temperature is 1200°C, the insulation time is 10 min, the heating rate is 100°C / min, and the axial pressure is 60 MPa.

[0034] The intelligent composite ceramic block prepared in this embodiment is ground to a thickness of 0.5 mm, and then its surface is polished, and then its surface is subjected to phase and composition analysis, mechanical properties, and nanomechanical behavior characterization, and the ceramic block is broken and its microstructure is observed through a cross-section.

[0035] Figure 2 is the arrangement diagram of graphene nanosheets in the GNPs / YSZ smart composite ceramic block. Figure 2 It can be seen that the direction of GNPs in the GNPs / YSZ smart composite ceramic block is consistent, and the arrangement direction of GNPs is perpendicular to the force direction of the composite ceramic block, which also shows that GNPs are successfully retained in the high-temperature sintered composite ceramics.

[0036] Figure 3 The XRD diagram of GNPs / YSZ smart composite ceramic powder is shown in Figure 2. Figure 3 The physical phases of GNPs and YSZ can be seen in the figure, which once again proves that GNPs are still retained after high-temperature sintering, and as the GNPs content increases, the GNPs peak becomes stronger.

[0037] Figure 4 Schematic diagram of hardness change of GNPs / YSZ smart composite ceramic block before and after high-energy electron irradiation. Figure 4 It can be seen that the hardness change percentage is improved by ∼97% compared to pure YSZ.

[0038] Figure 5 Schematic diagram of the change of fracture toughness of GNPs / YSZ smart composite ceramic block before and after high-energy electron irradiation. Figure 5It can be seen that the percentage change in fracture toughness increases by -206% compared to pure YSZ.

[0039] Embodiment 2:

[0040] This embodiment provides a method for preparing a GNPs / YSZ smart composite ceramic, the method comprising the following steps:

[0041] Step 1: Using planetary ball milling, 99.2 g of nano-scale GNPs powder, 0.8 g of YSZ powder, and 200 ml of 99.7% anhydrous ethanol are uniformly mixed to obtain a mixed solution B, and then dried at 80°C for 20 h in a blast drying oven to obtain a GNPs / YSZ composite ceramic powder, wherein: the YSZ powder is 8 mol% Y2O3-stabilized ZrO2 with a size of 40 nm; the GNPs powder has a thickness of 2 nm, and the length and width are 600 nm and 900 nm respectively; during the planetary ball milling, the ball-to-material mass ratio is 8:1, the ball milling time is 5 h, and the rotation speed is 200 r / min.

[0042] Step 2: Use spark plasma sintering technology to sinter the dried GNPs / YSZ composite ceramic powder to obtain a GNPs / YSZ intelligent composite ceramic block with a diameter of 24 mm and a thickness of 3.7 mm, wherein: the sintering temperature is 1300°C, the insulation time is 5 min, the heating rate is 130°C / min, and the axial pressure is 50 MPa.

[0043] Figure 4 Schematic diagram of hardness change of GNPs / YSZ smart composite ceramic block before and after high-energy electron irradiation. Figure 4 It can be seen that the hardness change percentage is increased by ∼74.9% compared to pure YSZ.

[0044] Figure 5 Schematic diagram of the change of fracture toughness of GNPs / YSZ smart composite ceramic block before and after high-energy electron irradiation. Figure 5 It can be seen that the percentage change in fracture toughness increases by ∼146.3% compared to pure YSZ.

[0045] Embodiment 3:

[0046] This embodiment provides a method for preparing a GNPs / YSZ smart composite ceramic, the method comprising the following steps:

[0047] Step 1: Use planetary ball milling to evenly mix 98.8g of nano-scale GNPs powder, 1.2g of YSZ powder, and 300ml of 99.7% anhydrous ethanol to obtain a mixed solution C, and then use a forced air drying oven to dry it at 90°C for 16h to obtain a GNPs / YSZ composite ceramic powder, wherein: the YSZ powder is 8mol% Y2O3 stabilized ZrO2 with a size of 50nm; the grain size of the YSZ powder is 50nm; the GNPs powder has a thickness of 3nm, a length of 800nm, and a width of 500nm; the vertical stirring time is 6h, the rotation speed is 600r / min, and the ball-to-material mass ratio is 10:1.

[0048] Step 2: Use spark plasma sintering technology to sinter the dried GNPs / YSZ composite ceramic powder to obtain a GNPs / YSZ intelligent composite ceramic block with a diameter of 25 mm and a thickness of 3.8 mm, wherein: the sintering temperature is 1400°C, the insulation time is 3 minutes, the heating rate is 150°C / min, and the axial pressure is 40 MPa.

[0049] Figure 4 Schematic diagram of hardness change of GNPs / YSZ smart composite ceramic block before and after high-energy electron irradiation. Figure 4 It can be seen that the hardness change percentage is reduced by 50% compared with pure YSZ.

[0050] Figure 5 Schematic diagram of the change of fracture toughness of GNPs / YSZ smart composite ceramic block before and after high-energy electron irradiation. Figure 5 It can be seen that the percentage change in fracture toughness increases by ∼278.8% compared to pure YSZ.

[0051] Embodiment 4:

[0052] This embodiment provides a method for preparing a GNPs / YSZ smart composite ceramic, the method comprising the following steps:

[0053] Step 1: Using planetary ball milling, 99.6 g of nano-scale GNPs powder, 0.4 g of YSZ powder, and 300 ml of 99.7% anhydrous ethanol are uniformly mixed to obtain a mixed solution A, and then dried at 70°C for 24 hours in a blast drying oven to obtain a GNPs / YSZ composite ceramic powder, wherein: the YSZ powder is 8 mol% Y2O3-stabilized ZrO2 with a size of 30 nm; the GNPs powder has a thickness of 1 nm, and the length and width are 500 nm and 1 μm, respectively; during the planetary ball milling, the ball-to-material mass ratio is 10:1, the ball milling time is 4 hours, and the rotation speed is 150 r / min.

[0054] Step 2: Use cold isostatic pressing and solid phase sintering technology to sinter the dried GNPs / YSZ composite ceramic powder to obtain a GNPs / YSZ intelligent composite ceramic block with a diameter of 25 mm and a thickness of 4 mm, wherein: the solid phase sintering temperature after cold isostatic pressing is 1300°C, the temperature is kept for 2 hours, the heating rate is 10°C / min, and the cold isostatic pressing axial pressure is 200 MPa.

Claims

1. A GNPs / YSZ smart composite ceramic, characterized in that The composite ceramic GNPs / YSZ composite ceramic block is formed by mixing GNPs powder and YSZ powder, the GNPs are arranged in the YSZ ceramic in a controllable direction, and the content of the GNPs is 0.1-2 wt.%.

2. The GNPs / YSZ smart composite ceramic according to claim 1, characterized in that The YSZ powder is 4-8 mol% Y2O3 stabilized ZrO2, and has a size of 10-100 nm.

3. The GNPs / YSZ smart composite ceramic according to claim 1, characterized in that The GNPs powder has a thickness of 1 to 3 nm, and a length and a width of 500 nm to 1 μm.

4. A method for preparing the GNPs / YSZ smart composite ceramic according to claims 1-3, characterized in that The method comprises the following steps: Step 1: using a planetary ball mill to uniformly mix nano-scale GNPs powder, YSZ powder and anhydrous ethanol to obtain a mixed solution, and then drying it in a blast drying oven to obtain GNPs / YSZ composite ceramic powder, wherein the mass ratio of the anhydrous ethanol to the GNPs / YSZ composite powder is 1 to 3:1; Step 2: Sinter the dried GNPs / YSZ composite ceramic powder using spark plasma sintering technology or solid phase sintering technology after cold isostatic pressing to obtain a dense GNPs / YSZ smart composite ceramic block, wherein: in the GNPs / YSZ smart composite ceramic block, the GNPs are arranged in a controllable direction in the YSZ ceramic, and the content of GNPs is 0.1 to 2wt.%.

5. The method for preparing the GNPs / YSZ smart composite ceramic according to claim 4, characterized in that During the planetary ball milling, the ball-to-material mass ratio is 5-10:1, the ball milling time is 3-12 hours, and the rotation speed is 150-300 r / min.

6. The method for preparing the GNPs / YSZ smart composite ceramic according to claim 4, characterized in that The drying temperature is 50-100° C. and the drying time is 12-24 hours.

7. The method for preparing the GNPs / YSZ smart composite ceramic according to claim 4, characterized in that The spark plasma sintering temperature is 1200-1400° C., the heat preservation time is 2-10 minutes, the heating rate is 100-150° C. / min, and the axial pressure is 30-60 MPa.

8. The method for preparing the GNPs / YSZ smart composite ceramic according to claim 4, characterized in that The temperature of the solid phase sintering after cold isostatic pressing is 1200-1400° C., the temperature is kept for 1-2 hours, the heating rate is 5-15° C. / min, and the axial pressure of cold isostatic pressing is 200-400 MPa.

9. The method for preparing the GNPs / YSZ smart composite ceramic according to claim 4, characterized in that The GNPs / YSZ intelligent composite ceramic block has a diameter of 20 to 25 mm and a thickness of 3 to 4.5 mm.

10. An application of the GNPs / YSZ smart composite ceramics according to claims 1-3 in extreme environments facing high temperature and space radiation.

Citation Information

Patent Citations

  • Composite powder composition for ceramic coating and ceramic coating, and preparation method thereof

    CN104725038A

  • Graphene-ceramic composite powder and preparation method thereof

    CN106747431A

  • A turbomachinery component with a metallic coating

    CN113574205A

  • Anisotropic silicon carbide conductive ceramic and preparation method thereof

    CN113831134A

  • High-emissivity infrared ceramic material as well as preparation method and application thereof

    CN114907118A